The Histone Database: a comprehensive WWW resource for histones and histone fold-containing proteins - Sullivan, Steven A. (Oxford University Press, 2000)
The Histone Database (HDB) is an annotated and searchable collection of all full-length sequences and structures of histone and non-histone proteins containing the histone fold motif. These sequences are both eukaryotic and archaeal in origin. Several new histone fold-containing proteins have been identified, including Spt7p, and a few false positives have been removed from the earlier version of HDB. Database contents include compilations of post-translational modifications for each of the core and linker histones, as well as genomic information in the form of map loci for the human histone gene complement, with the genetic loci linked to Online Mendelian Inheritance in Man (OMIM). Conflicts between similar sequence entries from a number of source databases are also documented. Newly added to the HDB are multiple sequence alignments in which predicted functions of histone fold amino acid residues are annotated. The database is freely accessible through the WWW at http://genome.nhgri.nih.gov/histones/